2009
DOI: 10.1227/01.neu.0000356972.97356.c5
|View full text |Cite
|
Sign up to set email alerts
|

Management of a Spontaneous Spinal Epidural Abscess

Abstract: Our data do not support the hypothesis that patients treated without early surgery are more likely to have a poor outcome. Furthermore, we propose that the anatomy of the SEA (ventral or dorsal) should play an important role in determining the treatment plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 8 publications
2
77
1
Order By: Relevance
“…7,12,14,18,27,37,41 Reportedly, SEA usually occurs in the thoracolumbar spine, dorsally. 19,30,31 In one study, systemic symptoms were more common among those with ventral lesions, and focal deficits were more common among those with dorsal lesions. 19 In the absence of contraindications, the standard imaging modality is MRI; CT myelography is an equivalent option.…”
Section: 10mentioning
confidence: 98%
See 3 more Smart Citations
“…7,12,14,18,27,37,41 Reportedly, SEA usually occurs in the thoracolumbar spine, dorsally. 19,30,31 In one study, systemic symptoms were more common among those with ventral lesions, and focal deficits were more common among those with dorsal lesions. 19 In the absence of contraindications, the standard imaging modality is MRI; CT myelography is an equivalent option.…”
Section: 10mentioning
confidence: 98%
“…3,17,21,33,43 Factors that can be associated with a worse prognosis are older age, diabetes mellitus, neurological and mental deterioration, and dorsal location of the SEA. 1,8,9,19,23,32 Additionally, higher reoperation and mortality rates are associated with renal failure and hemodialysis. 44,45 In terms of pathogenic microorganisms, overwhelmingly the most common is S. aureus, followed by Streptococcus spp.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…14, 15 Savage et al 16 reported that medical treatment with antibiotics is a viable alternative to surgery for patients without systemic sepsis or neurological symptoms. However, the limited literature does not clarify the role and outcome of medical treatment or surgical intervention, 17 particularly in patients with ESRD, and thus close clinical follow-up is required. All patients with neurologic deficit should undergo urgent spinal decompression and abscess drainage.…”
Section: Discussionmentioning
confidence: 99%